Temporary migration, transformation and development evidence from Europe and Asia - Pitkänen, Pirkko 1954-; Hayakawa, Tomoko 1973-; Schmidt, Kerstin 1971-; Aksakal, Mustafa 1973- (Routledge, 2019)
"In a world grappling with refugee crisis, political unrest and economies on the verge of collapse, temporary migration has become an increasingly common phenomenon. This volume presents a comprehensive picture of the transformative and development potential of temporary transnational migration in political, legal, economic, social and cultural aspects. This book: - Analyses how temporary migration is distinct from more permanent and circular forms of migration; - Brings together case studies from five Asian countries (China, India, the Philippines, Thailand and Turkey) and six European countries (Finland, Germany, Greece, Hungary, the Netherlands and Ukraine) - Based on exhaustive interviews of over 800 migrants, returnees and migrants' family members along with about 300 field experts, politicians, authorities and actors in civil society; - Illustrates the diverse nature of temporary migration, the continuing globalisation of the labour market and the interrelated changes to immigration, integration and emigration policies on local, national and international scales. This volume will be of indispensable to scholars and researchers of development studies, international politics, international relations, migration and diaspora studies, public policy, sociology and social anthropology. It will also be of importance to government think-tanks and NGOs working in the area"--